2021
DOI: 10.1002/cphc.202100435
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expression of a Carbazole‐Phenothiazine Derivative Leads to Dual‐mode AIEE, TADF and Distinctive Mechanochromism

Abstract: In this article, we report a newly designed DÀ AÀ D' derivative (CNCzPTZ), which displays selective expression of chromophores. This enables CNCzPTZ with solvatochromism, rare dualmode AIEE properties, solid-state dual-emissions with phosphorescence and distinctive mechanochromism.CNCzPTZ exhibits dual-mode AIEE properties, since the emission band abruptly shifts from 550 nm to 500 nm as the water fraction increases. In the crystalline state, CNCzPTZ demonstrated dual emission bands of 478 nm and 538 nm.CNCzPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Phosphorescence selective expression in the development of UORTP materials to enrich the properties and functions of smart materials is a very interesting topic but has not been realized yet due to the lack of organic phosphorescence units. In this work, we report a new phosphorescence unit 7 H -benzo­[c]­carbazole (BCz) from easy synthesis. BCz derivatives (PNBCz-1 and PNBCz-2) feature photoactivated green ultralong phosphorescence in the PMMA film at room temperature, and cation radicals are involved in the unique ultralong phosphorescence behavior, which function similarly with Bd derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorescence selective expression in the development of UORTP materials to enrich the properties and functions of smart materials is a very interesting topic but has not been realized yet due to the lack of organic phosphorescence units. In this work, we report a new phosphorescence unit 7 H -benzo­[c]­carbazole (BCz) from easy synthesis. BCz derivatives (PNBCz-1 and PNBCz-2) feature photoactivated green ultralong phosphorescence in the PMMA film at room temperature, and cation radicals are involved in the unique ultralong phosphorescence behavior, which function similarly with Bd derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison to previously studied PTZ and Cz analogy gives valuable context for understanding the unexpected optical behaviours of the new materials. For PTZ in particular, its geometric "butterfly wing" folding distortions enabled by the larger atomic radius of sulphur relative to oxygen [17,18], were expected to prevent molecular aggregation and provide high HOMO electron densities [19][20][21][22]. In both molecules we observe J o u r n a l P r e -p r o o f dual CT emission with enhanced delayed fluorescence from the PTZ CT state.…”
Section: Introductionmentioning
confidence: 86%
“…Hasan et al reported the carbazole and phenothiazine based derivative 25 (Chart 2). 108 The pristine sample of 25 exhibited two emission bands at 478 nm and 538 nm, which corresponded to the charge-transfer emission of the carbazole moiety and the fluorescence and TADF of the phenothiazine moiety (quasi-equatorial conformation). Upon mechanical grinding, the peak at 538 nm disappeared and the ICT peak of the carbazole was bathochromically shifted to 525 nm.…”
Section: Phenothiazinementioning
confidence: 96%